Comprehensive therapy approach for patients affected by chloride dioxide and chlorine derivative poisoning - Tapia-Ibáñez, Elvia Ximena (2022)
During the sanitary emergency due to SARS-CoV-2, and considering the absence of specific therapy against this condition, many therapy approaches with no underlying scientific evidence appeared, leading to infodemics with many publications about the use of chloride dioxide and chlorine derivatives, without any regulation on manufacturing, distribution, and administration of such products; and so many people developed multiple symptoms, leading to intoxication and death. In this context, this paper aims to offer healthcare personnel, a comprehensive pre-hospital therapy approach for patients affected by the aforementioned compounds. The idea is to perform a protocol where the scenario for patients’ exposure is determined (use of personal protective equipment, triage, decontamination, and the like), primary and secondary assessments are to be performed (continuously reassessing the affected patient). Later, hospital management is to be performed (systematic patient’s assessment, identifying the exposure route and use of an antidote when necessary for specific cases); and establishing prevention measures for both healthcare personnel and the general population.